Profile of selected cytokines in various forms of uveitis - Rusiecka-Ziółkowska, Jolanta; Turno-Kręcicka, Anna; Białek-Szymańska, Anna; Salomon, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The estimation of the level of selected inflammatory mediators in serum of patients with various types of uveitis. Material and methods: The level of IL-1, IL-6 and TNF was assessed by means of microbiological tests and ELISA test in the group of 60 patients with uveitis, divided as regards to the character of uveitis and the type of the treatment and in control group. Results: The levels of IL-1, IL-6 and TNF were higher in serum of patients with uveitis then in the control group. Patients with known etiology of uveitis had higher level of IL-6 and TNF. Patients with autoimmunological etiology of uveitis had higher level of IL-1 and IL-6 than volunteers in control group. Conclusions: Higher levels of cytokines in serum of patients with uveitis than in control group indicate the activation of immunological response in various types of uveitis.